VARIABEL ANTESEDEN DAN KONSEKUENSI DARI KINERJA KUALITAS (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DENGAN BERSERTIFIKAT ISO 9000) - Handayani, Dwi (Widya Warta, 2011)
The purpose of this study is to investigate the influence of quality management control systems (quality goal, quality feedback, quality incentives) and environmental accounting on quality performance. The data used in this research were collected from finance, marketing, and production managers of manufacture companies with ISO 9000.The data collecting was done by mail survey on 483 questionnaries. The questionnaires which were relevant for the analysis were 113 in number. The data analysis was conducted by the use of SEM with AMOS ver. 5.0. The result shows that communication intensity of quality goal toward the labourers was not related to quality performance. The frequency of quality feedback was not related to quality performance. The improvement of incentives in relation to quality had a positive relationship with quality performance. The implementation of environmental accounting had no relationship with quality performance. Quality performance had no relationship with customer satisfaction. Quality performance had a positive relationship with financial performance. Customer satisfaction had a positive relationship with financial performance.